A Fantástica Fábrica de Chocolate: uma abordagem narrativa sobre o cinema digital - Marina de Morais Faria Novais (2014)
This research has as objective to analyze the contributions that digital format can bring to the telling of two film adaptations of the book Charlie and the Chocolate Factory, written by Roald Dahl. For this, the study compares both productions, made in 1971s and 2005s, directed by Mel Stuart and Tim Burton, and produced in analog and digital formats, respectively. Moreover, both are compared, in some parts, with the foundation of the literary work of Dahl. Thus, primarily the research makes a historical review of changing technologies in cinema. After there is a descriptive and interpretive analyzes of sequences of the movies that have a notable similarity. In these moments of analysis the research looks for constants and variables generated by differences in technology between cinema of the 1970s and 2000s, beyond different stylistic approaches of the filmmakers, among other factors. Finally, there is a reflection about what implications the digital format brought to the film, in terms of both visual and sound elements, but also in terms of narrative and plot. The digital version can build more details of the story and tell it in a linear form, through the use of visual effects and computer simulations, while the version in analog format requires a lot of cutting and some changes in narrative structure to follow the proposal of the book. The rhythm of the narrative of each film is also different, the digital version has a much lower amount of plans, which also reflects on the implications of the format on process of construction of narrative and film editing.. The main authors of this research are: Ismail Xavier, Jacques Aumont, Lev Manovich, David Bordwell, Pierre Lévy and Edmond Couchot, in order of relevance inside the study.